Сборник зарубежной фантастики - Бондаренко И.М. (Детектив. Приключения. Фантастика, 1992)
Экземпляры: ф. 1 (20090225) / Инвентарный номер: 93853 / Цена: 30.00 / Авт.знак: С 23 / ГРНТИ: 17.82 / ББК: 84(7Сое)